IP-CHOCK (filter)-Based detection scheme for Denial of Service (DoS) attacks in VANET - Verma, K. (Institute of Electrical and Electronics Engineers Inc., 2014)
The vehicular ad-hoc Network (VANET) has drawn increasing attention in recent years due to its wide range of applications. At the present time, a vehicle's communication is exposed to many security threats such as Denial of Service (DoS) attacks, in which a malicious node forges a large number of fake identities. Internet Protocol (IP) spoofing of addresses - is initiated to disrupt the proper functioning of the fair data transfer between two fast moving vehicles. In this paper, the Bloom-filter-based detection method, which provides the availability of a service for the legitimate vehicles in the VANET, as used to detect and defend against the IP spoofing of addresses of the DoS attacks. The IP spoofing of addresses in the DoS attacks which is committed by fraudulent and malicious nodes has been investigated. This method provides a secure communication and also frees the bandwidth. This proposed approach requires fewer resources and is easy to deploy. Simulation results have shown that this method is efficient and effective to defend against and detect DoS attacks. Specifically, this method provides a faster detection time, lower storage capacity and computational cost. Â© 2014 IEEE.